Debt as Safe Asset - Markus K. Brunnermeier; Sebastian Merkel; Yuliy Sannikov (Center for Economic Studies and ifo Institute (CESifo), 2021)
The price of a safe asset reflects not only the expected discounted future cash flows but also future service flows, since retrading allows partial insurance of idiosyncratic risk in an incomplete markets setting. This lowers the issuers' interest burden and allows the government to run a permanent (primary) deficit without ever paying back its debt. As idiosyncratic risk rises during recessions, so does the value of the service flows bestowing the safe asset with a negative ß. This resolves government debt valuation puzzles. Nevertheless, the government faces a "Debt Laffer Curve". The paper also has important implications for fiscal debt sustainability.
Keywords: 330; safe asset; government debt; Debt Laffer Curve; Ponzi Scheme; fiscal capacity; I Theory of Money; r vs. g